Pengaruh kualitas produk dan harga terhadap kepuasan pelanggan Kopi Starbucks di Summarecon Mall Kelapa Gading 3 - Jerry Prasadana Putra; Sitinjak, Tumpal Janji Raja (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The development of society at this time has experienced changes in lifestyle (lifestyle). This lifestyle change has greatly influenced the mindset, behavior and culture of the community, one of which is the habit of certain community groups who like to gather in cafes or coffee shops. There are several customer reviews about product quality and product prices, therefore it is necessary to do this research to determine the Effect of Product Quality and Price on Customer Satisfaction Starbucks Coffee at Summarecon Mall Kelapa Gading 3. The independent variables in this study are product quality and price while the dependent variable in this study is customer satisfaction. This research was conducted by distributing questionnaires to customers who consumed Starbucks Coffee at Summarecon Mall Kelapa Gading 3 in the last 6 months in February 2022 via Google Form. The data obtained from the results of the questionnaire distribution were analyzed using descriptive tests, validity tests, reliability tests, classical assumption tests, and multiple linear regression tests and then processed using the SPSS version 20 program. The results showed that respondents strongly agreed that the product quality and price of Starbucks Summarecon Mall Kelapa Gading is good. This study found that product quality and price had a positive and significant effect on customer satisfaction. The conclusion of this study is that the variables of product quality and price have a positive and significant effect on Starbucks customer satisfaction at Summarecon Mall Kelapa Gading 3.